Incorporating facilitative interactions into small‐scale eelgrass restoration—challenges and opportunities. Issue 5 (5th May 2021) - Gagnon, Karine; Christie, Hartvig; Didderen, Karin; Fagerli, Camilla W.; Govers, Laura L.; Gräfnings, Max L. E.; Heusinkveld, Jannes H. T.; Kaljurand, Kaire; Lengkeek, Wouter; Martin, Georg; Meysick, Lukas; Pajusalu, Liina; et al.
Abstract : Marine ecosystem engineers such as seagrasses and bivalves create important coastal habitats sustaining high biodiversity and ecosystem services. Restoring these habitats is difficult due to the importance of feedback mechanisms that can require large‐scale efforts to ensure success. Incorporating facilitative interactions could increase the feasibility and success of small‐scale restoration efforts, which would limit pressure on donor sites and reduce costs and time associated with restoration. Here, we tested two methods for providing facilitation in small‐scale eelgrass ( Zostera marina ) restoration plots across northern Europe: (1) co‐restoration with blue mussels ( Mytilus edulis, M. trossulus ); and (2) the use of biodegradable establishment structures (BESEs). Eelgrass‐mussel co‐restoration showed promise in aquaria, where eelgrass growth was nearly twice as high in treatments with medium and high mussel densities than in treatments without mussels. However, this did not translate to higher shoot length or shoot densities in subsequent field experiments. Rather, hydrodynamic exposure limited both eelgrass and mussel survival, especially in the most exposed sites. The use of BESEs showed more potential in enabling small‐scale restoration success: they effectively enhanced eelgrass survival and reduced mussel loss, and showed potential for enabling mussel recruitment in one site. However, eelgrass planted in BESE plots along with mussels had a lower survival rate than eelgrass planted in BESE plots without mussels. Overall, we show that though co‐restoration did not work at small scales, facilitation by using artificial structures (BESEs) can increase early eelgrass survival and success of small‐scale eelgrass and bivalve restoration.